INTEGRATING JOYFUL LEARNING PRINCIPLES IN TASK-BASED LANGUAGE TEACHING TO BUILD STUDENTS’ PARTICIPATION IN ENGLISH CLASS AT SMPN 2 SIMPENAN - Stadela; Anisa Septia Megawati; Usman Diennur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student participation is an important aspect of successful English language learning, activities. However, many students are reluctant to participate actively due to low motivation, lack of confidence, and limited opportunities for meaningful interaction. This study aimed to investigate how joyful learning principles integrated into Task-Based Language Teaching (TBLT) build students’ participation in English classes and to identify the challenges encountered during its implementation. This study employed a qualitative case study design. Data were collected through classroom observations, student interviews, and teacher interviews and analyzed using Miles and Huberman’s interactive model of qualitative data analysis. The findings revealed that integrating joyful learning principles within TBLT encouraged students’ behavioral, cognitive, and emotional engagement. Students actively participated in learning activities, collaborated with peers, completed assigned tasks, and engaged in discussions and problem-solving. Students also stated that enjoyable and interactive activities made them feel more comfortable, motivated, confident, and willing to participate. In addition, these learning activities provided meaningful opportunities for students to communicate, collaborate, and express their ideas in a supportive classroom environment. Several challenges were identified, including classroom management, differences in students’ motivation, confidence, and language proficiency, difficulties in designing tasks, and time constraints. Overall, the findings indicate that integrating joyful learning principles into TBLT supported students’ participation by creating a more engaging learning environment.